Amorphous Zinc Stannate (Zn2SnO4) Nanofibers Networks as Photoelectrodes for Organic Dye-Sensitized Solar Cells - Choi, Seung-Hoon; Hwang, Daesub; Kim, Dong-Young; Kervella, Yann; Maldivi, Pascale; Jang, Sung-Yeon; Demadrille, Renaud; Kim, Il-Doo (WILEY-V C H VERLAG GMBH, 2013)
A new strategy for developing dye-sensitised solar cells (DSSCs) by combining thin porous zinc tin oxide (Zn2SnO4) fiber-based photoelectrodes with purely organic sensitizers is presented. The preparation of highly porous Zn2SnO4 electrodes, which show high specific surface area up to 124 m(2)/g using electrospinning techniques, is reported. The synthesis of a new organic donor-conjugate-acceptor (D--A) structured orange organic dye with molar extinction coefficient of 44 600 M-1 cm(-1) is also presented. This dye and two other reference dyes, one organic and a ruthenium complex, are employed for the fabrication of Zn2SnO4 fiber-based DSSCs. Remarkably, organic dye-sensitized DSSCs displayed significantly improved performance compared to the ruthenium complex sensitized DSSCs. The devices based on a 3 m-thick Zn2SnO4 electrode using the new sensitizer in conjunction with a liquid electrolyte show promising photovoltaic conversion up to 3.7% under standard AM 1.5G sunlight (100 mW cm(-2)). This result ranks among the highest reported for devices using ternary metal oxide electrodes.